2021
DOI: 10.1371/journal.pone.0253282
|View full text |Cite
|
Sign up to set email alerts
|

Acromioplasty reduces critical shoulder angle in patients with rotator cuff tear

Abstract: Critical shoulder angle (CSA) is the angle between the superior and inferior bone margins of the glenoid and the most lateral border of the acromion and is potentially affected during a rotator cuff tear (RCT). Acromioplasty is generally performed to rectify the anatomy of the acromion during RCT repair surgery. However, limited information is available regarding the changes in the CSA after anterolateral acromioplasty. We hypothesized that CSA can be decreased after anterolateral acromioplasty. Data were retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Anterolateral acromioplasty was described in 2 studies. Lin et al [ 25 ] reported that 337 participants presented with a mean CSA of 38.4° ± 6.0° before surgery, which significantly decreased to 35.8° ± 5.9° after anterolateral acromioplasty ( p < 0.05). Katthagen et al [ 17 ] reported that anterolateral acromioplasty decreased the CSA by a mean of 1.4° (95% CI 0.8°, 1.9°).…”
Section: Resultsmentioning
confidence: 99%
“…Anterolateral acromioplasty was described in 2 studies. Lin et al [ 25 ] reported that 337 participants presented with a mean CSA of 38.4° ± 6.0° before surgery, which significantly decreased to 35.8° ± 5.9° after anterolateral acromioplasty ( p < 0.05). Katthagen et al [ 17 ] reported that anterolateral acromioplasty decreased the CSA by a mean of 1.4° (95% CI 0.8°, 1.9°).…”
Section: Resultsmentioning
confidence: 99%
“…48,49 The role of acromioplasty in the setting of RCT repair has been widely discussed. Lin et al 50 showed that anterolateral acromioplasty effectively reduced CSA and this is more significant among individuals with CSA ≥ 38 degrees than among those with CSA < 38 degrees. Conversely, Thiesemann et al 51 concluded that anterolateral acromioplasty did not result in a significant change in the CSA; a significant reduction was observed in the case of CSA > 35 degrees but not to normal values.…”
Section: Discussionmentioning
confidence: 99%